2015
DOI: 10.1136/archdischild-2015-308483
|View full text |Cite
|
Sign up to set email alerts
|

Five-minute Apgar score and educational outcomes: retrospective cohort study of 751 369 children

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
27
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 33 publications
7
27
2
1
Order By: Relevance
“…19 A low Apgar score 20 -a commonly used indicator of health in the immediate neonatal period -has been shown to be associated with increased neonatal and infant mortality 21 and additional educational support needs in later life. 22 Considerable attention has been focused on the causal determinants of low birthweight in order to identify potentially modifiable factors. A substantial proportion of low birthweight is attributable to the mother's cultural and socioeconomic circumstances, such as socioeconomic status (SES), harmful behaviours (smoking and excessive alcohol consumption) and poor nutrition during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…19 A low Apgar score 20 -a commonly used indicator of health in the immediate neonatal period -has been shown to be associated with increased neonatal and infant mortality 21 and additional educational support needs in later life. 22 Considerable attention has been focused on the causal determinants of low birthweight in order to identify potentially modifiable factors. A substantial proportion of low birthweight is attributable to the mother's cultural and socioeconomic circumstances, such as socioeconomic status (SES), harmful behaviours (smoking and excessive alcohol consumption) and poor nutrition during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Apgar scores (≤3) and special needs due to physical and motor impairment. 25 It has been suggested that birth around 40 weeks is associated with the lowest risk of developmental vulnerability 26 and special needs. 24 Overall, we found no difference in educational achievement of the children at ages 5 and 8, although children with special needs were exempt from testing.…”
Section: Discussionmentioning
confidence: 57%
“…25 It has been suggested that birth around 40 weeks is associated with the lowest risk of developmental vulnerability 26 and special needs. 25 It has been suggested that birth around 40 weeks is associated with the lowest risk of developmental vulnerability 26 and special needs.…”
Section: Discussionmentioning
confidence: 99%
“…For more than 60 years, it has been used to measure the condition of newborn infants based on heart rate, respiration, colour, muscle tone and reflex irritability (1). Subsequent studies have demonstrated the Apgar score's ability to predict short-term and long-term cognitive outcomes (2,3) as well as developmental impairment (4,5). As an index of early neonatal conditions and health, the Apgar score could, in theory, also be used as a measure of stressful exposures during delivery and early life.…”
Section: Introductionmentioning
confidence: 99%